Discovery of a Unique Flavonoid Biosynthesis Mechanism in Fungi by Genome Mining. (9th February 2023) - Zhang, Wei; Zhang, Xuan; Feng, Dandan; Liang, Yajing; Wu, Zhenying; Du, Siyu; Zhou, Yu; Geng, Ce; Men, Ping; Fu, Chunxiang; Huang, Xuenian; Lu, Xuefeng
Abstract: Flavonoids are important plant natural products with variable structures and bioactivities. All known plant flavonoids are generated under the catalysis of a type III polyketide synthase (PKS) followed by a chalcone isomerase (CHI) and a flavone synthase (FNS). In this study, the biosynthetic gene cluster of chlorflavonin, a fungal flavonoid with acetolactate synthase inhibitory activity, was discovered using a self‐resistance‐gene‐directed strategy. A novel flavonoid biosynthetic pathway in fungi was revealed. A core nonribosomal peptide synthetase‐polyketide synthase (NRPS‐PKS) is responsible for the generation of the key precursor chalcone. Then, a new type of CHI catalyzes the conversion of a chalcone into a flavanone by a histidine‐mediated oxa‐Michael addition mechanism. Finally, the desaturation of flavanone to flavone is catalyzed by a new type of FNS, a flavin mononucleotide (FMN)‐dependent oxidoreductase. Abstract : Plant flavonoids are synthesized by type III PKS followed by chalcone isomerase (CHI) and flavone synthase (FNS). Now a unique flavonoid biosynthesis mechanism has been identified in fungi by genome mining. The chalcone skeleton is assembled by an NRPS‐PKS hybrid enzyme, and subsequent conversion into a flavone is catalyzed by new types of CHI and FNS. This finding provides new insight into the microbial production of valuable plant flavonoids.